INFORMAL ACTORS AS FEATURE OF A NEW WORLD ORDER - Evelina Anatolievna Emuzova (Современная наука и инновации)
In article the role of informal actors in a new world order is considered. It is claimed that today the concept of a new world order contacts not time frames, and informal agents. Informal agents, global elite or other similar groups have the increasing impact on world affairs.